SET‐NUP214 and MLL cooperatively regulate the promoter activity of the HoxA10 gene. (8th August 2021) - Cigdem, Sadik; Saito, Shoko; Nishikata, Daiki; Nagata, Kyosuke; Okuwaki, Mitsuru
Abstract: SET‐Nup214 is a recurrent fusion gene that is mainly observed in T‐cell acute lymphoblastic leukemia (T‐ALL). Dysregulation of homeobox ( Hox ) genes is frequently observed in patients with leukemia. Consistent with this, HoxA genes are upregulated in the SET‐Nup214 + T‐ALL cell line and patients. Although SET‐Nup214 has been reported to be recruited to the promoter regions of HoxA genes, the detailed mechanisms of how SET‐Nup214 specifically binds to HoxA gene promoters and regulates HoxA gene expression are not known. In this study, we demonstrated that SET‐Nup214 interacts with MLL via the SET acidic region of SET‐Nup214. SET‐Nup214 and MLL cooperatively enhance the promoter activity of the HoxA10 gene. Neither the SET region alone nor the Nup214 region alone sufficiently enhanced the HoxA10 gene promoter. Our results indicated that the SET portion of the SET‐Nup214‐fusion protein is important for interactions with MLL and transcription enhancement of the HoxA10 gene. Thus, our study will contribute to the understanding of how SET‐Nup214 and MLL disturb the expression of HoxA10 gene in leukemia. Abstract : SET‐Nup214 fusion protein, mainly observed in T‐cell acute lymphoblastic leukemia, interacts with MLL. SET‐Nup214 and MLL cooperatively enhance the promoter activity of the HoxA10 gene.